SELF ACCEPTANCE AND SIGNIFICANT OTHER AS PSYCHOSOSIAL RESOURCES FOR FEMALE NARRANT RESILIENCE WITH LIFETIME PENALTIES - Imaduddin Hamzah (Polteknik Ilmu Pemasyarakatan, 2018)
Punishment while in prison places individuals in a limited environment and experiences pressure. Conditions of pressure can be felt even higher when inmates experience a life sentence. This study aims to explore the factors of resilience of female prisoners with life sentences. Research using semi-structured interviews of five female inmates at the Women Correctional Institution, Malang punished with life imprisonment. Data were analyzed with a qualitative interpretative phenomenological analysis approach. The results of the study conclude that the factors that make female prisoners resilient to life sentences are self acceptance and significant other.